NEPOTISME DALAM PENGUASAAN SUMBER DAYA POLITIK DAN EKONOMI: STUDI KASUS PENYELENGGARAAN PEMERINTAHAN DESA SEROSAH KECAMATAN HULU KUANTAN KABUPATEN KUANTAN SINGINGI - Kaffah, Fhisilmi; ", Adlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The implementation of the Serosah Village administration (2015-2020) has resulted in various polemics in the community. The phenomenon is that the implementation of the duties and functions carried out by the Serosah Village Government is not in accordance with existing provisions resulting in abuse of power and indications of nepotism practices carried out by the Serosah Village Government.The act of nepotism is carried out when there is a recruitment process and a job selection process. The aim of this research was to find out and discuss the nepotism of control over political and economic resources, the Headman of Desa Serosah Kecamatan Hulu Kuantan Kabupaten Kuantan Singingi in the administration of village governance.This research used the theory of nepotism according to Cottingham (1986). Nepotism can be seen from two perspectives, namely from the perspective of its relationship forms (Kinshipism, Familism, Clanism, Patriotism, Racism, Sexism, Planetism) and from an ethical perspective (favoritism, Discrimination, Partiality Justice. Merit system). The research method used in this research is qualitative research. This type of research was descriptive qualitative research. The research location was in the desa serosah, kecamatan hulu kuantan, kabupaten kuantan singingi. The results of the research carried out were that the headman of the Serosah village took nepotism in the implementation of the village governance. The headman of Serosah assigned positions to his children, families and relatives and control the political and economic resources in Serosah village for personal gain. The headman of Serosah in the process of recruitment and selection of positions was based on aspects of descent and who sided with him. Â Keywords : Nepotism; Recruitmen; Headman